COMPARISON BETWEEN THE M.ED. CURRICULA OF PUBLIC AND PRIVATE UNIVERSITIES OF BANGLADESH - MD. Abdullah Al-Mamun Patwary (LPPM UNY, 2009)
This research study was aimed at (1) comparing the Master of Education (M.Ed.) curricula of public universities and private universities of Bangladesh, and (2) identifying the similarities and dissimilarities along with the strengths and weaknesses of these curricula. Data and information necessary for the study were collected from the M.Ed. curricula of 2 public and 3 private universities of Bangladesh. Only qualitative analyses were done in examining the documentary information. A comparative method was employed to organize and analyze the information. Findings of the study revealed that the structures of the M.Ed. curricula of public universities were more organized than those of private universities. The objectives prescribed in the M.Ed. curricula of public university were more specific than those of private universities; and the objectives of the public university were stated in terms of measurable behavior.